A Comparative Study on Haematological Changes before and One hour after Haemodialysis in Patients with End Stage Renal Disease - Rahman, Md Moshiur; Giti, Susane; Khan, Arif Ahmed; Rahman, Md Mizanur; Tarek, Monwar; Bhuiyan, Mohammed Nuruzzaman (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Normal kidney function is very important for maintaining homeostasis. Any deviation of normal renal function leads to deviation of normal homeostasis. End-stage renal disease (ESRD) is the last stage of chronic kidney disease (CKD) resulting from different aetiologies. Different haematological abnormalities in patients with ESRD result from multiple pathogenesis. Treatment of this condition requires multidisciplinary approach. Among all the treatment options haemodialysis (HD) is the most common, widely accepted and available treatment option. Objective: To find out the effectiveness of haemodialysis in the improvement of different haematological deviations developed during the course of ESRD. Materials and Methods: A total of 72 patients with ESRD of both sexes with the age ranging from 25 years to 70 years were included in this comparative cross sectional study and carried out in Combined Military Hospital and Armed Forces Institute of Pathology, Dhaka Cantonment from November 2014 to October 2015. Results: The pre dialysis haematological parameters found in this study were TRBC: 3.4 ± 0.5 X 1012/L, haemoglobin (Hb) level : 9.5 ± 1.4 gm/dL, Haematocrit (HCT): 29.1 ± 4.4%, Mean corpuscular volume (MCV): 83.5 ± 7 fl, Mean corpuscular Hb (MCH): 28 ± 1.8 pg, Mean corpuscular Hb concentration (MCHC): 31.0 ± 2.9 gm/dl, Total leucocyte count (TLC): 6.6 ± 1.9 X109/L, Neutrophil: 66.3 ± 7.8 %, Lymphocyte: 24.5 ± 6.9 %, Monocyte: 5.0 ± 1.8%, Eosinophil: 4.1 ± 2.4 %, Platelet: 184.3 ± 66.5 X 109/L. One hour post HD values are: TRBC: 3.6 ± 0.6 X1012/L, Hb level:10.1 ± 1.6 gm/dl, Hct: 30.9 ± 5 %, MCV:82.6 ± 6.9 fl, MCH: 29.1 ± 2.3 pg, MCHC: 32.2 ± 3.4 gm/dl,TLC: 7.3 ± 2.3 X 109/L, Neutrophil: 69.2 ± 7 %, Lymphocyte: 21.6 ± 5.5 %, Monocyte: 5.3 ± 2 %, Eosinophil: 3.9 ± 2.3%. Platelet: 206.1 ± 63.6 X109/L. Among these values TRBC, Hb level, Hct, MCH, MCHC, TLC, Neutrophil, Lymphocyte and Platelet count significantly improved after HD (p value < .05). Conclusion: Haemodialysis in the management of patients with CKD/ESRD played a pivotal role in improving haematological parameters deranged by these conditions. JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 39-42